Emergence of a substrate-temperature-dependent dielectric process in a prototypical vapor deposited hole-transport glass - Rodríguez-Tinoco, Cristian (Sci Rep, 2018)
Since the discovery of ultrastability, vapor deposition has emerged as a relevant tool to further understand the nature of glasses. By this route, the density and average orientation of glasses can be tuned by selecting the proper deposition conditions. Dielectric spectroscopy, on the other hand, is a basic technique to study the properties of glasses at a molecular level, probing the dynamics of dipoles or charge carriers. Here, and for the first time, we explore the dielectric behavior of vapor deposited N,N-Diphenyl-N,N’bis(methylphenyl)-1,1′-biphenyl-4,4′-diamines (TPD), a prototypical hole-transport material, prepared at different deposition temperatures. We report the emergence of a new relaxation process which is not present in the ordinary glass. We associate this process to the Maxwell-Wagner polarization observed in heterogeneous systems, and induced by the enhanced mobility of charge carriers in the more ordered vapor deposited glasses. Furthermore, the associated activation energy establishes a clear distinction between two families of glasses, depending on the selected substrate-temperature range. This finding positions dielectric spectroscopy as a unique tool to investigate the structural and electronic properties of charge transport materials and remarks the importance of controlling the deposition conditions, historically forgotten in the preparation of optoelectronic devices.